A real-world study of ublituximab based on the WHO-VigiAccess and U.S. food and drug administration’s adverse event reporting system databases - Cao, Jiagnang; Shen, Qinguo; Zou, Yan (Frontiers in Immunology, 2026)
ObjectiveThe study bridge statistical pharmacovigilance signals to clinically actionable insights by systematically characterizing adverse event (AE) patterns associated with ublituximab and identifying previously unrecognized risks. We aim to establish a quantitative framework to inform real-world safety monitoring protocols and regulatory risk-benefit evaluations.MethodsWe systematically analyzed AE reports associated with ublituximab through a comprehensive retrospective study of FAERS and VigiAccess databases (data cutoff: December 29, 2024). Utilizing five validated disproportionality analysis methods—the Reporting Odds Ratio (ROR), Proportional Reporting Ratio (PRR), Bayesian Confidence Propagation Neural Network (BCPNN), Medicines and Healthcare Products Regulatory Agency algorithm (MHRA), and Multi-Item Gamma Poisson Shrinker (MGPS).ResultsOur investigation integrated 2, 245 case reports from the FAERS with 2, 037 entries in VigiAccess database. Signal detection via the ROR and PRR uncovered 52 preferred term (PT)-level signals significantly associated with ublituximab in the FAERS database, corresponding to 20 system organ class (SOCs). Notably, four SOCs - encompassing cardiovascular disorders, vascular pathologies, urinary system conditions, and social environment factors - were identified with disproportionality signals but currently lack documentation in approved prescribing information. We identified 8 frequently reported PTs (hypoaesthesia, fall, gait disturbance, paraesthesia, balance disorder, alopecia, tremor, and somnolence) within the top 50 AEs showed disproportionality signals but remain unlisted in the current drug lable.ConclusionThis study has identified confirmed positive signals associated with ublituximab and revealed potential signals of interest. These findings highlight the need for further regulatory review to assess whether the identified signals justify updates to drug labeling and therapeutic guidelines. Future investigations should build upon the AE signals established in this research, with further investigations warranted to elucidate both the clinical incidence rates of these AEs and their definitive causal relationships with ublituximab.